Research on Return Forecasting and Portfolio Construction in China’s A-Share Market: Based on CAPM and Fama-French Three-Factor Models - Wang Xinyi (SHS Web of Conferences)
This research investigates Capital Asset Pricing Model and Fama-French three-factor model effectiveness of return prediction and portfolio optimization for the Chinese A-share market. The empirical observation from January 2020 to December 2024 of shares listed on the Shanghai and Shenzhen stock exchanges validates FF3’s superior explanatory power compared to CAPM. Different selection portfolios demonstrate statistically significant non-zero alphas for specifications of FF3. Evidence supports the existence of local variables to fit inefficiencies in emerging markets and supports periods of style rotation to be addressed through the utilization of momentum-enhanced models. However, the model to apply has to be chosen depending on specific market situations and investment objectives. In cases of high market volatility, FF3 is superior, while the CAPM is comparatively good during stable markets. In addition, negative Sharpe ratios and non-zero alphas under the FF3 model are signs of unexplained variables and potential inefficiencies in portfolio methods. Future research can examine the inclusion of other risk factors, such as liquidity or momentum, to further enhance the models’ predictive capabilities for China’s A-share market.